Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 51825 by Abdo msup. last updated on 30/Dec/18

find f(α)=∫_0 ^1 ln(1+e^(−α) x)dx  with α≥0

findf(α)=01ln(1+eαx)dxwithα0

Commented by maxmathsup by imad last updated on 31/Dec/18

let put e^(−α)  =λ ⇒f(α)=∫_0 ^1 ln(1+λx)dx and by parts u^′ =1 ,v=ln(1+λx)  we get f(α) =[xln(1+λx)]_0 ^1  −∫_0 ^1  x (λ/(1+λx))dx  =ln(1+λ)−∫_0 ^1  ((λx+1−1)/(1+λx))dx =ln(1+λ)−1 +∫_0 ^1   (dx/(1+λx))  =ln(1+λ)−1 +(1/λ)ln∣1+λx∣ +c ⇒  f(α)=ln(1+e^(−α) )−1 +e^(−α) ln∣1+e^(−α) x∣ +c .

letputeα=λf(α)=01ln(1+λx)dxandbypartsu=1,v=ln(1+λx)wegetf(α)=[xln(1+λx)]0101xλ1+λxdx=ln(1+λ)01λx+111+λxdx=ln(1+λ)1+01dx1+λx=ln(1+λ)1+1λln1+λx+cf(α)=ln(1+eα)1+eαln1+eαx+c.

Commented by maxmathsup by imad last updated on 31/Dec/18

f(α)=ln(1+e^(−α) )−1 +e^α ln∣1+e^(−α) x∣ +c .

f(α)=ln(1+eα)1+eαln1+eαx+c.

Commented by Abdo msup. last updated on 31/Dec/18

f(α)=ln(1+λ)−1+[(1/λ)ln∣1+λx∣]_0 ^1  +c  =ln(1+λ)−1 +(1/λ)ln(1+λ)+c  ⇒f(α)=ln(1+e^(−α) )−1+e^α ln(1+e^(−α) )+c  =(1+e^α )ln(1+e^(−α) )−1+c  .

f(α)=ln(1+λ)1+[1λln1+λx]01+c=ln(1+λ)1+1λln(1+λ)+cf(α)=ln(1+eα)1+eαln(1+eα)+c=(1+eα)ln(1+eα)1+c.

Answered by Smail last updated on 30/Dec/18

let  t=1+e^(−α) x⇒dx=e^α dt  f(α)=e^α ∫_1 ^(1+e^(−α) ) ln(t)dt  by parts  u=ln(t)⇒u′=(1/t)  v′=1⇒v=t  f(α)=e^α [tlnt]_1 ^(1+e^(−α) ) −e^α ∫_1 ^(1+e^(−α) ) dt  =e^α ((1+e^(−α) )ln(1+e^(−α) )−e^(−α) )  f(α)=(e^α +1)(ln(e^α +1)−α)−1

lett=1+eαxdx=eαdtf(α)=eα11+eαln(t)dtbypartsu=ln(t)u=1tv=1v=tf(α)=eα[tlnt]11+eαeα11+eαdt=eα((1+eα)ln(1+eα)eα)f(α)=(eα+1)(ln(eα+1)α)1

Terms of Service

Privacy Policy

Contact: info@tinkutara.com